Community/Public Health Nurses' Awareness of Residential High-Rise Fire Safety issues - Gary Glauberman PhD, RN, PHNA-BC; Kristine Qureshi PhD, RN, CEN, PHNA-BC, FAAN (SAGE Publishing, 2021)
High-rise (HR) building fires remain a tragic cause of preventable injury and death in the United States. Recent incidences of HR building fires have served as high-profile reminders of the persistent threat that HR fires pose to public health. Fire safety is an important aspect of household emergency preparedness addressed by community/public health nurses (C/PHNs). This study aimed to address a gap in the literature regarding C/PHNs' awareness of fire safety for people and families who reside in HR buildings. A descriptive qualitative study using key-informant and focus group interviews was conducted involving C/PHNs ( n   =  19) in Honolulu, Hawaii. Qualitative data analysis revealed three main themes related to this issue: (1) C/PHN awareness of HR fire safety issues, (2) C/PHN perceived barriers for HR building occupant fire safety, and (3) C/PHN suggested strategies to address HR fire safety for occupants. Findings highlight how more needs to be done to assure that C/PHNs are adequately prepared to work with occupants of residential HR buildings on matters related to fire safety.